Participation in breast cancer prevention: assessing women's knowledge and their participation in mammography in Tehran, Iran - Ahmadian, Maryam; Abu Samah, Asnarulkhadi; Redzuan, Ma'rof; Emby, Zahid (Academic Journals, 2012)
A survey was carried out from July through October, 2009 to study the knowledge and women’s participation in mammography. A total of 400 women in urban areas of Tehran, Iran were randomly selected in this study. Although, the general knowledge of women was fairly good, they did not participate in mammography in the last 2 years. However, the mean score of the knowledge of women who were adherent to mammography was higher than the non-adherent group. These responses provide evidence that health education on breast cancer screening knowledge is necessary for future participation in breast cancer prevention programs in Iran.